Navigating Digital Challenges: The Role of Self-Efficacy in Coping with Technostress in Remote Regions - Christy Kartini Tonoro; Prio Utomo (Green Publisher Indonesia, 2026)
The rapid expansion of digital technologies has reshaped higher education, creating both opportunities and pressures for lecturers, particularly in resource-constrained regions. This study explores the phenomenon of technostress and its impact on lecturers' self-efficacy in Terdepan, Terluar, dan Tertinggal (3T) regions. Based on the Person–Environment Fit Theory and self-efficacy theory, the research investigates how lecturers experience and respond to digital demands amid infrastructure limitations. Using a qualitative phenomenological design, nine lecturers from diverse disciplines participated in in-depth interviews. Thematic analysis revealed five interrelated dimensions: techno-overload, techno-complexity, techno-uncertainty, the mediating role of self-efficacy, and institutional and cultural support. Digitalisation intensified workloads, platform complexity challenged senior lecturers lacking formal training, and unstable systems increased uncertainty. Higher self-efficacy fostered adaptive coping, whereas lower self-efficacy encouraged avoidance strategies. Findings highlight that technostress in underdeveloped higher education settings is not only an individual struggle but also a systemic issue shaped by weak infrastructure, inconsistent institutional support, and cultural dynamics. While self-efficacy strengthens resilience, it cannot offset structural inequities. The study extends the technostress literature in underdeveloped regional contexts and highlights the need for sustained infrastructure investment, structured training, and culturally grounded mentors to support inclusive digital transformation.